2016
DOI: 10.4103/1742-6413.173585
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration diagnosis of secondary tumors involving the pancreas: An institution's experience

Abstract: Background:Pancreatic masses may seldom represent a metastasis or secondary involvement by lymphoproliferative disorders. Recognition of this uncommon occurrence may help render an accurate diagnosis and avoid diagnostic pitfalls during endoscopic ultrasound-guided fine needle aspiration (EUS-FNA). In this study, we review our experience in diagnosing secondary tumors involving the pancreas.Materials and Methods:The electronic database of cytopathology archives was searched for cases of secondary tumors involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 45 publications
2
57
1
Order By: Relevance
“…[910] As stated above, it is very unusual for UC to metastasize to the pancreas, with only rare reports diagnosed by FNA in the literature in addition to those we reported [Table 1]. Canter et al .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[910] As stated above, it is very unusual for UC to metastasize to the pancreas, with only rare reports diagnosed by FNA in the literature in addition to those we reported [Table 1]. Canter et al .…”
Section: Discussionmentioning
confidence: 63%
“…also only described one case of UC that had metastasized to the pancreas between 2005 and 2012, out of the 1346 patients who had undergone EUS-FNA with ROSE for pancreatic lesions at Yale University. [10] This patient was a 69-year-old female who apparently had a known prior history of malignancy and previous bladder resection and presented with a solitary lesion of the pancreatic body after a 2-year latent period. Due to prior resection, this patient had histological evidence of the primary malignancy which confirmed the cytological diagnosis, so no ancillary studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies of series of pancreatic metastases diagnosed by FNA/CNB were reported between 1992 and 2016 (Table ). The study durations were 2–26 years and included 112–5495 pancreatic FNA/CNB . Only 11–66 metastases were detected in these reports, comprising only 0.7%‐11.1% of all FNA/CNB and 1.8%‐10.8% of all neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) guided FNA is a minimally invasive procedure which reduces associated hemorrhage and potential infection, as a result of direct visualization and sampling of smaller amounts of tissue . Additionally, EUS‐guided FNA proffers high accuracy, and the ability to detect lesions smaller than 1 cm . With the advent and increased utilization of EUS, we have observed the diminution of computerized tomographic (CT) guided pancreas biopsies in our institution.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation